Factors Affecting Presentation Delay to the Hospital Among Breast Cancer Patients: A Retrospective Analysis - Kajal Nehra; Jisa George T; Geeta Bhardwaj; Rajesh Pasricha (Journal of Family and Reproductive Health)
Objective: Breast cancer constituted 13.5% of all reported new cancer in India, with a notable mortality rate due to late presentation.  The current research aims to address the extent of delay in presentation to the hospital and the factors that contribute to delayed presentation among breast cancer patients. Materials and methods: A descriptive cross-sectional study was conducted among 138 primary breast cancer patients aged 18 to 60 years, with a time lag of more than 2 weeks between the initial recognition of symptoms and the first medical interaction. These patients were attending the oncology Outpatient Department (OPD) of tertiary care center in Central India, where female breast cancer patients receive treatment and follow-up care. The analysis employed binary logistic regression to assess the factors significantly affecting the delayed presentation to the hospital. Results: Most of the participants were aged between 40 and 50 years and did not have a family history of breast cancer. The median delay in presentation to the hospital was 2 months. Women having breast lump as initial breast symptom tend to present late (> 3 months) to the hospital (p=0.037) and if the breast lump was smaller, they are more likely to delay seeking medical attention compared to those with larger breast lump (p=0.012). Conclusion: The study indicates that many patients delayed seeking help due to small breast lumps. Improved screening services are needed for early detection. Future awareness campaigns should emphasize the link between breast lumps and cancer to reduce delays and improve patient quality of life.